RETRACTED: Product Market Competition and Firm Performance: Business Survival Through Innovation and Entrepreneurial Orientation Amid COVID-19 Financial Crisis - Liu, Qiang; Qu, Xiaoli; Wang, Dake; Abbas, Jaffar; Mubeen, Riaqa (Frontiers in Psychology, 2022)
The product market competition has become a global challenge for business organizations in the challenging and competitive market environment in the influx of the COVID-19 outbreak. The influence of products competition on organizational performance in developed economies has gained scholars' attention, and numerous studies explored its impacts on business profitability. The existing studies designate mixed findings between the linkage of CSR practices and Chinese business firms’ healthier performance in emerging economies; however, the current global crisis due to the coronavirus has made product market completion fierce, which ultimately affects business firms' performance. This study focuses on this logical global challenge, investigates the rationale, and examines product-market completion impact on firms’ performance operating in the Chinese markets. The study collected data from the annual reports of Chinese business organizations with A-share listing and registered with the database of China Stock Markets & Accounting Research (CSMAR). The study employed a Generalized Method of Moment technique and investigated the connection between product market competition and Chinese firm performance. The empirical analysis of this study highlights the conclusion that market competition positively and significantly affected business firms' performance. This study specified that product market competition play a dynamic and indispensable role in achieving healthier firm performance in the Chinese markets. This study provides valuable insights on practical implications and future research directions for the scholars to draw interesting results with new study models.